Performance analysis of zero-forcing coordinated MIMO transmission in interference channels - Hai-rong WANG; Jian DONG; Yong-ming HUANG; ANGLV-xi Y (Tongxin xuebao)
The performance of the zero-forcing (ZF) coordinated transmit strategy in multiple-input multiple-output (MIMO) interference channels was investigated.With the goal to derive analytical expression of its performance metric such as the sum rate and the outage probability,the asymptotic behavior of the performance metric was examined with the MIMO dimension tending to infinity.Using the random ma ix theory,an asymptotic estimate of all the eigenvalues of the effective channel matrix in the ZF coordinated transmit strategy was first proposed.Based on that,two closed-form expressions of the sum rate were derived,from which the scaling law of the sum rate with the MIMO dimension was obtained.Furthermore,using the multivariate statistics about the probability density distribution of the minimum eigenvalue of a Wishart matrix,the analytical expression of the outage probability for the coordinated transmit scheme was achieved under two special cases.Simulation results show that the proposed tical expression of the performance metric is valid not only in the large-dimension regime,but also in the normal-dimension regime.